Customer Switching Intention: The Integrated Framework of Disconfirmation Theory - Widya Prananta; Vitradesie Noekent; Angga Pandu Wijaya; Bayu Bagas Hapsoro (Media Ekonomi dan Manajemen, 2023)
Due to growing competition, customer retention has become a big problem in many service companies. Within a conceptual model for consumer switching intention, this article examines the influence of customer experience, customer satisfaction, and switching intention to green products, all of which are controlled by online information. Even though scholars have researched consumer switching intentions and the elements that influence them, the complex structural processes that minimize the chance of switching intentions in higher education institutions have remained unstudied. This paper addresses the role of customer experience and customer satisfaction to switching intentions moderated by online information. Data is collected through a questionnaire survey. This study employs purposive sampling to obtain respondents (n = 135), with the criteria, students at Universitas Negeri Semarang, a Conservatory University, who wish to switch to green products. Empirical findings support the proposed model and hypotheses, demonstrating that (1) customer satisfaction is negatively related to switching intention, and (2) The online information factor further strengthens the relationship between customer satisfaction and switching intention. The findings of this study provide a unified understanding of the structural relationships that contribute to increased green switching intention to the development of disconfirmation theories in the higher-education context. Implementing a green campus within Universitas Negeri Semarang, campus communities are encouraged to switch to environmentally friendly products to support green campus policies.